Rotator cuff tears. Issue 3 (March 2016) - Vollans, Sam; Ali, Amjid
Abstract: Rotator cuff tears are a common cause of pain and weakness in the shoulder. We describe the anatomy and function of the normal rotator cuff, before an overview of cuff tears, with reference to their incidence and pathogenesis. Finally, we discuss clinical presentation, examination findings, treatment options and the prognosis of cuff tears. The authors of this article hope to enable the reader to understand rotator cuff disease, assess patients with suspected rotator cuff tears and discuss the basic treatment options with patients.